Reconstructing sedimentary environments of MR1 core and investigating facies’ geotechnical properties through the piezocone penetration test in the Late Pleistocene-Holocene periods in the Mekong River Delta - Hoang, Truong Minh; Lap, Nguyen Van; Oanh, Ta Thi Kim; Jiro, Takemura (VNU Journal of Science: Earth and Environmental Sciences, 2010)
Abstract. The aim of the study was to reconstruct sedimentary environments of the MR1 core and investigate geotechnical properties of sedimentary facies through the piezocone penetration test (CPTU). A core at the Vinhlong province, Mekong River Delta (MRD), sufficiently presented the Holocene facies of the area. Eight facies were identified based upon sedimentary properties. Characteristics of the units showed development of sedimentary facies. Each sedimentary facies was formed under different environment. Each sedimentary facies presents CPTU results differently. A facies has various sedimentarystructures and materials such as the estuarine channel, estuarine marine, and delta front mouth bar facies; values of cone resistance, q t , sleeve friction, f s , and pore water pressure, u 2 , in its CPTU results will increase highly, vary largely, and present in saw-tooth shape in the overall plot of them as a function of depth. A facies’ sedimentary property is highly homogeneous such as the marsh, bay, and prodelta facies; its values of q t , f s , and u 2 increase almost linearly with depth. Keywords: Vinhlong; Late Pleistocene-Holocene; MRD; facies’ geotechnical properties; CPTU.